Modeling Soil Lateral Deformation Due to Water Film using Smoothed Particle Hydrodynamics - Bahsan, Erly; Soepandji, Budi Susilo; Rahayu, Wiwik; Marthanty, R.R. Dwinanti R.; Ontowirjo, Budianto (UI Scholars Hub, 2024)
In geotechnical engineering, large deformation in soil materials is rarely simulated using numerical methods, particularly the finite element method and finite difference method, because they experience difficulties in representing the postfailure soil behavior. As an alternative to these methods, the smoothed particle hydrodynamics (SPH) method has recently been adopted to represent soil behavior. The SPH method is a Lagrangian, mesh-free numerical method in which the materials are modeled as a set of particles. In this method, soil behavior can be represented via the Drucker–Prager elasto–plastic failure criterion. Thus, this method can be used to simulate postfailure soil behavior and large deformation in soil materials. This study attempts to analyze large deformation of soil due to an extremely gentle slope and a thin water layer (referred to as the water film). The model is simulated using a C++ platform called PersianSPH. The results demonstrate that lateral deformation can occur in such a geometry because of the effective stress changes during liquefaction.